A Family of Heat Functions as Solutions of Indeterminate Moment Problems - Ricardo Gómez; Marcos López-García (International Journal of Mathematics and Mathematical Sciences)
We construct a family of functions satisfying the heat equation and show how they can be used to generate solutions to indeterminate moment problems. The following cases are considered: log-normal, generalized Stieltjes-Wigert, and q-Laguerre.